Femtosecond laser based deposition of nanoparticles on a thin film and its characterization - Kokaj, Jahja; Shuaib, Ali; Makdisi, Yacoub; Nair, Remya; Mathew, Joseph (Kuwait Journal of Science, 2018)
Femtosecond laser based deposition of nanoparticles is a promising technique for the formation of homogenous thin films. The introduction provides a literature review related to the techniques for thin film deposition including pulsed-laser deposition (PLD). We then describe the homemade chamber used for PLD with a femtosecond laser. An atomic force microscope (AFM) was used to measure the characteristics of the obtained films. Thickness, roughness and texture of the surface of the films were visualized using this technique. X-ray diffraction and scanning electron microscopy were used to characterize the obtained thin layer of nanoparticle film. The band gap energy of zinc oxide film was determined using UV-VIS characterization,